2017
DOI: 10.4236/ajibm.2017.72007
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review about the Influence Factors of Self-Employment

Abstract: The laborer's employment form can be subdivided into wage-employment, self-employment and unemployment. Self-employment can also be called entrepreneurship, in response to the statement "Public entrepreneurship, Peoples innovation" put forward by the prime minister Li Keqiang. In recent years, self-employment has been attracting more and more attention of researchers, and becomes the research hot spot problem. Self-employment plays an important role in reducing poverty, fostering innovation, developing entrepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…Algunos trabajos han investigado la elección que toma una persona de auto emplearse sobre sus oportunidades profesionales tradicionales (Wan, 2017). Es así que varios autores argumenten que los individuos eligen el autoempleo como una opción profesional si las ganancias económicas derivadas de esta opción son superiores a las ganancias económicas de ser empleado (Al-Qadasi et al, 2021).…”
Section: Revisión De La Literaturaunclassified
“…Algunos trabajos han investigado la elección que toma una persona de auto emplearse sobre sus oportunidades profesionales tradicionales (Wan, 2017). Es así que varios autores argumenten que los individuos eligen el autoempleo como una opción profesional si las ganancias económicas derivadas de esta opción son superiores a las ganancias económicas de ser empleado (Al-Qadasi et al, 2021).…”
Section: Revisión De La Literaturaunclassified
“…There are many studies analysing the educational model in countries of origin and how it affects the success or otherwise of students (Dheer, 2017;Kangasharju & Pekkala, 2002;Padilla-Mel endez et al, 2014;Reilly, 2013;Wan, 2017). According to Morales (2006), the programmes are effective when the primary objective is for young people to participate in an education that trains them, both in educational terms and in the attainment of basic skills, and which fosters their processes of transition and integration towards adult, social, educational and productive life (Morales, 2006).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Research was carried out in many fields such as economics, psychology, sociology and business management to determine how an individual engages in self-employment. Previous findings revealed that family and social characteristics (Wan, 2017;Wolfe and Patel, 2017) influence the individual's engagement in self-employment. In addition, personality (Chlosta et al, 2012), trait (Ekelund et al, 2005), cognitive factors (Kolvereid and Isaksen, 2006), risk-taking (Stewart and Roth, 2001) and demographic factors (Leoni and Falk, 2010) play a crucial role in determining individual's engagement in self-employment.…”
Section: Literature Reviewmentioning
confidence: 99%